2017
DOI: 10.1161/circresaha.116.309140
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Genomics of Congenital Heart Disease

Abstract: Congenital heart disease is the most common birth defect, and due to major advances in medical and surgical management, there are now more adults living with CHD than children. Until recently, the cause of the majority of CHD was unknown. Advances in genomic technologies have discovered the genetic etiology of a significant fraction of CHD, while at the same time pointing to remarkable complexity in CHD genetics. This review will focus on the evidence for genetic causes underlying CHD and discuss data supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
432
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 396 publications
(468 citation statements)
references
References 152 publications
9
432
1
5
Order By: Relevance
“…Epigenetics play a nonignorable role in fetal development. It has been reported that histone methylation plays important roles in cardiac lineage specification and differentiation [25], heart development [5,26], and the pathogenesis of congenital and adult heart diseases [2,27,28]. Histone deacetylase activity controls valvulogenesis in zebrafish by promoting myocardial expression of Bmp4 at the atrioventricular boundary [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetics play a nonignorable role in fetal development. It has been reported that histone methylation plays important roles in cardiac lineage specification and differentiation [25], heart development [5,26], and the pathogenesis of congenital and adult heart diseases [2,27,28]. Histone deacetylase activity controls valvulogenesis in zebrafish by promoting myocardial expression of Bmp4 at the atrioventricular boundary [29].…”
Section: Discussionmentioning
confidence: 99%
“…CHD can be divided into nonsyndromic phenotypes, including gene mutations, and syndromic phenotypes, including chromosomal abnormalities, such as Down's syndrome, Edwards syndrome, and Patau syndrome. Only about one-third of CHD cases have been described as clear genetic or chromosomal abnormality cases [2,3]. The causes of CHD are complex and involve interaction among the environment, genetics, and epigenetics.…”
Section: Introductionmentioning
confidence: 99%
“…In general, de novo mutations are more deleterious and cause more significant comorbidities than the mutations seen in Mendelian CHD (43). De novo mutations primarily cause CHD by altering critical developmental pathways shared by multiple developing organ systems, such as: chromatin remodeling (a critical process for regulating gene expression) and Notch signaling (instrumental for local intercellular communication in a variety of organ systems), (11, 4448). The next section will show that mutations affecting these pathways provide a genetic explanation not only of CHD but also for the of some of the comorbidities that affect long term outcomes in CHD patients.…”
Section: The Genetics Of Chdmentioning
confidence: 99%
“…Figure 2 presents an algorithm for clinicians to use when beginning a genetics evaluation of a CHD patient (11). The key to efficient and appropriate testing of CHD patients is the clinical context of the patient.…”
Section: Genetic Testing In Chd Patientsmentioning
confidence: 99%
See 1 more Smart Citation